Rulings On Taking The Fare On Hajj And Umrah: Malaysia As A Model - Mohamed Rashid Ab Razak; Abdul Manan Ismail (Usuli Faqih Research Centre PLT, 2024)
Al-Qanatir: International Journal of Islamic Studies. Vol. 11. No. 1 Page (55-70)